Phenotypic and Performance Characterization of Aravali Breed of Chicken - Savaliya, Fulabhai P.; Bhagora, Nikesh J.; Patel, Atul B.; Kathiria, Keshubhai B. (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The study was carried out to characterize native chickens of North Gujarat recently registered as “Aravali” breed of chicken for phenotypic  and performance traits from field and farm levels. Observations were recorded as per the format of National Bureau of Animal Genetic  Resources (NBAGR). Data collected at farm level and from field level, by survey work were analyzed. The proportion of black breasted  silver-red plumage colour was highest for male and the buff-brown plumage colour in females at both field and farm level. Plumage  pattern in males and females was birchen and shafty, respectively. Pre-dominantly red ear lobe was observed in males and white ear lobe  in females. Body weight of adult male and female field birds was 1990.56 g and 1618.05 g, respectively while at the end of 40th week,  male and female body weight was found to be 2001.80 g and 1593.57 g, respectively on farm. Age at first egg was found to be 6.25 and  5.67 months at field and farm level, respectively. Annual egg production recorded was 72.36 at field level and 95.04 at farm level upto  56 weeks of age. Clutch size and clutch intervals were 18.11 and 92.03 days, respectively, at field level. Egg weight and shell thickness  were higher and intensity of the yolk colour was lower at farm level as compared to field level. Dressing percentage was higher in males  as compared to the females. Fertility and hatchability were higher at field level as compared to farm level for Aravali breed of chicken.  Key words: Aravali breed of chicken, Carcass characteristics, Growth characteristics, Phenotypic traits, Plumage.
Keywords: Aravali breed of chicken; Carcass characteristics; Growth characteristics; Phenotypic traits; Plumage